2007
DOI: 10.1016/j.jtbi.2007.07.025
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for human nucleotide excision repair: Damage recognition by random order assembly and kinetic proofreading

Abstract: A mathematical model of human nucleotide excision repair was constructed and validated. The model incorporates cooperative damage recognition by RPA, XPA, and XPC followed by three kinetic proofreading steps by the TFIIH transcription/repair factor. The model yields results consistent with experimental data regarding excision rates of UV photoproducts by the reconstituted human excision nuclease system as well as the excision of oligonucleotides from undamaged DNA. The model predicts the effect that changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
(69 reference statements)
1
18
1
3
Order By: Relevance
“…This model also invokes a cooperativity function in binding to achieve a higher specificity for damaged DNA. This specificity is enhanced by the kinetic proofreading activity of TFIIH to verify the recognition step [28]. This represents an interesting treatment of the damage recognition step in NER and highlights the importance of the kinetics of the interactions.…”
Section: Recognition Of Dna Damage By Ner Factorsmentioning
confidence: 90%
See 1 more Smart Citation
“…This model also invokes a cooperativity function in binding to achieve a higher specificity for damaged DNA. This specificity is enhanced by the kinetic proofreading activity of TFIIH to verify the recognition step [28]. This represents an interesting treatment of the damage recognition step in NER and highlights the importance of the kinetics of the interactions.…”
Section: Recognition Of Dna Damage By Ner Factorsmentioning
confidence: 90%
“…Using a model without including RPA as a recognition factor indicates that a sequential ordered process results in the most efficient excision [27]. More recent modeling however favors a random order-cooperative binding/kinetic proofreading model [28]. This model incorporates RPA as a recognition factor and includes potential dissociation of NER factors, and supports RPA, XPA and XPC-RAD23B assembly at the site of damage.…”
Section: Recognition Of Dna Damage By Ner Factorsmentioning
confidence: 99%
“…While the precise order of addition of the damage recognition factors remains somewhat controversial [7], the favored working model for GGR is described below and see Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous biochemical and cell biological studies have confirmed that checks for different structural abnormalities in DNA are conducted in a sequential manner. Additionally, possible stochastic mathematical models have been also discussed (Kesseler et al, 2007;Luijsterburg et al, 2010;Politi et al, 2005). Considering the in vivo situations, decondensation and some remodeling of the chromatin structure would also be expected to precede damage recognition by UV-DDB and XPC, although the underlying mechanism involved in this process remains unclear.…”
Section: Resultsmentioning
confidence: 99%